Overview of universal design application and accessibility in major cities of ASEAN countries - Abdul Rahim, Asiah; Abd Samad, Nur Amirah; Che Rahim, Che Raiskandar (2015)
The objective of this paper is to oversee the application of Universal Design and accessibility for people with disabilities (PwDs) in several major cities of ASEAN countries that are Malaysia, Thailand and Singapore. Previous studies show that the ageing and disabled population in this region increasing rapidly. In addition the aged population above 65 years by 2050 showed a high percentage. If any of the government and private sectors of each countries are not prepared to facilitate their infrastructure with good facilities for PwDs, buildings typologies on various use such education, workplace, recreational and tourist spots, sports facilities, transportation hubs be it on sea, land and airport, and various types of physical facilities, thus users especially the people with disabilities (wheelchair users, vision impaired, hearing impaired, those who are walking using stick and those who have learning difficulties) at the end will lose their opportunity to be at par with other developed countries in terms to have better quality of life, work opportunity and others which able bodies should enjoy their lives. Most of ASEAN countries are members of United Nation Economic and Social Commission of Asia Pacific (UNESCAP) and most have signed Proclamation Decade for People With Disabilities 1993-2002, and 2003 – 2012, and therefore these countries should implemented all listed items written in Biwako Millenium Framework (BMF) for Action Towards and Inclusive, Barrier Free and Right Based Society for Persons with Disabilities in Asia and The Pacific, October 2002 and for the next current decade, the declaration on the Asian and Pacific Decade of Persons with Disabilities, 2013–2022, and the Incheon Strategy to “Make the Right Real” for Persons with Disabilities in Asia and the Pacific.